Cameroon : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1996)
This Selected Issues paper and Statistical Appendix presents an overview of economic developments in Cameroon in 1994/95 and 1995/96. After nearly a decade of economic decline, real GDP grew by more than 3 percent in 1994/95 (July/June) and by an estimated 5 percent in 1995/96. Inflation, on an end-of-period basis, decelerated to 13 percent in 1994/95 and to 4 percent in 1995/96. Fiscal performance strengthened considerably, with government revenue rising by about 4 percentage points of GDP between 1993/94 and 1995/96, and total expenditure declining by 6 percentage points, to 17 percent of GDP in 1995/96.